Analysis of the Role of Internal Audit in Preventing and Detecting (Fraud) in Financial Statements - Bahar, Nurfadjriani; Rerung, Oktaviani Intan; Aulia, Indika Nurul; Herman, Nabila Tryana Putri; Asrul, Sitti Marwah; Oktaviyah, Nurafni (Phinisi Applied Accounting Journal, 2025)
This study discusses the role of internal audit in preventing and detecting financial statement fraud, given the increasing number of cases that undermine investor confidence and corporate integrity. The focus of the study is the effectiveness of internal audit as the first line of defense against fraud, especially in the context of Indonesian companies, which is still rarely studied. The research uses a literature study method from various journals and reports. The results show that independent and sustainable internal audit can significantly minimize the risk of fraud. In conclusion, strengthening the internal audit function plays a strategic role in maintaining the credibility of financial statements and corporate governance.Keywords: Internal Audit, Detection, Fraud, Financial Statements,Penelitian ini membahas tentang peran audit internal dalam mencegah dan mendeteksi kecurangan laporan keuangan, mengingat semakin banyaknya kasus yang merusak kepercayaan investor dan integritas perusahaan. Fokus penelitian adalah efektivitas audit internal sebagai garis pertahanan pertama terhadap kecurangan, terutama dalam konteks perusahaan Indonesia, yang masih jarang diteliti. Penelitian ini menggunakan metode studi pustaka dari berbagai jurnal dan laporan. Hasil penelitian menunjukkan bahwa audit internal yang independen dan berkelanjutan dapat meminimalkan risiko kecurangan secara signifikan. Kesimpulannya, penguatan fungsi audit internal memegang peranan strategis dalam menjaga kredibilitas laporan keuangan dan tata kelola perusahaan.Kata kunci: Internal Audit, Deteksi, Kecurangan, Laporan Keuangan